POPULASI DAN INTENSITAS SERANGAN HAMA PUTIH (Nymphula depunctalis Guene) PADA TANAMAN PADI SAWAH DI KECAMATAN DUMOGA TIMUR KABUPATEN BOLAANG MONGONDOW - Stela F. Pratiwi; Noni Wanta; Caroulus Rante; Guntur Manengkey (Universitas Sam Ratulangi, 2014)
ABSTRACTRice crops is included into the family of Graminae that produces seeds from China. Rice Plant is the crops that produce rice, consumed approximately by 90 % from the whole citizens of Indonesia as the main food. White pest(Nymphula depunctalis Guene) is one of pests that attacks rice crops in Indonesia. This research aims to find out the population and intensity of the attack of N. depuntalis pest. The research took place in sub-district of East Dumoga, regency of Bolaang Mongondow, which was in three villages, that is Imandi, Mogoyunggung and Tonom, and the execution time was from July to Desember 2013. This research used the survey method done in rice field belonged to farmers, each village was taken three observation plot, and determined of five sub observation plot to be observed.The materials and tools used were rice crops planting, killing bottle, indicator, insect net, insect collecting bottle, label paper, plastic bag, plastic rope, bamboo, pair of scissors,camera and writing tools. The research result shows that white pest (N. depunctalis) has been spread on the rice in three villages in sub-district of East Dumoga with the population average value of 2,16%. The highest pest population was found in Village of Mogoyunggung that is 2,93 pests on average, and then in village of Tonom with 2,28 pestsand the lowest population was found in village of Imandi with the average of 1,28 pests, while the attack intensity is still classified into the low one in sub-district of East Dumogathat is 10,33%.Keyword: rice plants, white pest, population, attack intensity